Global trends in the halal beauty and skincare industry: A search engine-based market analysis - Koswara, Asep; Herlina, Lina (International Journal of Halal Industry, 2025)
Purpose – This study explores global trends in halal beauty and skincare industries by analyzing search engine data. As consumer interest in ethical and halal-certified beauty products continues to rise, this research aims to identify key market patterns, regional demand variations, and brand influences that shape the industry. Methodology – A qualitative research approach was employed using Google Trends as the primary tool to track search interest over five years. Keywords related to halal cosmetics, skincare, and beauty products were analyzed to capture fluctuations in consumer engagement across various regions, both in Muslim-majority and non-Muslim-majority countries. Findings – The results reveal a steady increase in global search interest in halal beauty and skincare, with noticeable spikes driven by new product launches, influencer endorsements, and regulatory changes. Southeast Asia remains a dominant market, but rising interest in non-Muslim regions, such as Japan and Slovakia, highlights the broader appeal of halal-certified products. Additionally, search trends indicate that skincare generates higher fluctuations in interest than general beauty products, reflecting its sensitivity to seasonal and promotional factors. Implications – These findings underscore the growing influence of halal beauty beyond religious boundaries and present opportunities for brands to expand their reach. Future research should explore the correlation between search interest and consumer purchasing behavior as well as the role of social media in shaping halal beauty trends. Originality – This study contributes to the limited research on halal beauty trends by utilizing a search engine-based market analysis, offering real-time insights into evolving consumer preferences in the global halal beauty industry.